Offsite construction: strategic priorities for shaping the future research agenda - Goulding, Jack; Rahimian, Farzad Pour; Arif, Mohammed; Sharp, Mark (Canadian Centre of Academic Art and Science, 2012)
Modern Methods of Construction (MMC), Offsite Manufacturing (OSM), and Offsite Production (OSP) are all umbrella terms cited as being possible panacea solutions for addressing time, quality and cost concerns often associated with ‘traditional’ construction. In this respect, these issues have been on the agenda for a while now, with no viable business process models or solutions [cf. traditional to manufacturing/installation] being proffered or promoted as a meaningful ways forward. In an attempt to address this, a focus group workshop was established with domain experts to explore industry uptake and multidisciplinary expectations and priorities within the AEC sector. This paper presents findings from this session, covering the relationships between people, process and technology - mapped against the three core silos of Design, Manufacturing and Construction. Research areas investigated embraced several integral issues, from information and process flows, through to production, risk, and market drivers and inhibitors. Research findings identified a high demand for technology adoption in the design and construction remits, and a need to change traditional thinking across the whole supply chain. Core findings and priorities are presented for industry reflection in order to shape the future research agenda in this area.